Interstitial pregnancy: a case report - Aafreen, Asna; Pankaj, Apoorv; Pankaj, Aprajita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Interstitial pregnancy is a life-threatening event. Strong clinical suspicion and prompt action can reduce maternal morbidity and mortality. Specific ultrasound features point towards the diagnosis. Various treatment modalities are available as there is no consensus for a treatment of choice. The management option depends upon the general condition of the patient and also on fact whether the ectopic pregnancy has ruptured or not. Here we present a case of an unruptured interstitial pregnancy.